Across-shift lung function variation in cottonseed oil workers - (:unkn) unknown (OXFORD UNIV PRESS, 2006)
Background The effects of cotton dust on pulmonary function among workers employed in cotton-spinning mills are well known. However, little data exist on the prevalence of this disorder in 'non-textile' cotton industries, including cottonseed oil mills, where high levels of exposure to dust have been demonstrated. Aims This study was performed in order to determine the across-shift and across-week decline of FEV1 and respiratory symptoms among workers in a cottonseed oil mill. Methods Sixty-six exposed and 48 unexposed workers of a cottonseed oil mill in Turkey were investigated by questionnaire and lung function test (LFT). LFTs were performed before and after shift on all the working days of the week. Acute airway response was defined as an across-shift decline in FEV1 of 5% or more on the first working day. Results Smoking was the only risk factor for having respiratory symptoms. Acute airway response was more frequently observed in the exposed group as compared to the unexposed group (OR = 6.2, 95% CI = 2.3-16.7). The median across-shift decline in FEV1 on the first day (120 ml) significantly improved on the following days (10, 50, 60 and -30 ml). Conclusion Smoking appears to be the main risk factor for having respiratory symptoms. Cottonseed dust may cause an acute pulmonary function decline on the first working day, but not on the following days of the week. This decline is associated with respiratory symptoms in exposed workers.
Keywords: byssinosis; cottonseed dust; lung function; occupational health; respiratory symptoms; DUST EXPOSURE; RESPIRATORY SYMPTOMS; TEXTILE WORKERS